2023
DOI: 10.3389/fimmu.2023.1214289
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific roles of NLRP3, inflammasome-dependent and -independent, in host defense, sterile necroinflammation, tissue repair, and fibrosis

Abstract: The NLRP3 inflammasome transforms a wide variety of infectious and non-infectious danger signals that activate pro-inflammatory caspases, which promote the secretion of IL-1β and IL-18, and pyroptosis, a pro-inflammatory form of cell necrosis. Most published evidence documents the presence and importance of the NLRP3 inflammasome in monocytes, macrophages, and neutrophils during host defense and sterile forms of inflammation. In contrast, in numerous unbiased data sets, NLRP3 inflammasome-related transcripts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…In general, inflammasomes are considered restricted to myeloid cells, including monocytes, macrophages, dendritic cells and neutrophils. However, the presence of the NLRP3 inflammasome components has also been reported in epithelial and parenchymal cells 7 …”
Section: Immune Cell Functions and Their Distinguishing Featuresmentioning
confidence: 99%
“…In general, inflammasomes are considered restricted to myeloid cells, including monocytes, macrophages, dendritic cells and neutrophils. However, the presence of the NLRP3 inflammasome components has also been reported in epithelial and parenchymal cells 7 …”
Section: Immune Cell Functions and Their Distinguishing Featuresmentioning
confidence: 99%
“…The Nlrp3 inflammasome has been recognized to be the most vital target for delaying/treating several disorders, as its activation is evoked through a wide range of stress inducers, such as pathogens, toxins, degenerative/dead cells and damaged DNA/RNA aggregates, which are called pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs) [17,22]. It has also been shown that multiple pathways and mechanisms can be involved in the activation of the Nlrp3 inflammasome depending upon cell/tissue types [37][38][39][40]. ROS have been identified to be one of the critical elements for Nlrp3 inflammasome activation [38,41].…”
Section: Introductionmentioning
confidence: 99%